Hybrid covalent adaptable networks from cross-reactive poly(ε-caprolactone) and poly(ethylene oxide) stars towards advanced shape-memory materials. Issue 21 (28th September 2021) - Caprasse, Jérémie; Riva, Raphaël; Thomassin, Jean-Michel; Jérôme, Christine
Abstract : The synthesis and properties of hybrid poly(ε-caprolactone) (PCL)–poly(ethylene oxide) (PEO) covalent adaptable networks have been investigated. Abstract : The synthesis and properties of hybrid poly(ε-caprolactone) (PCL)–poly(ethylene oxide) (PEO) covalent adaptable networks have been investigated. This novel material uniquely combines recycling and reconfiguration capabilities with temperature and water-triggered shape-memory properties. Firstly, 4-arm star-shaped PEO and PCL were end-capped with furan and maleimide moieties, respectively. Then, equimolar mixtures of these cross-reactive stars were melt-blended and cured leading to PCL–PEO hybrid networks by Diels–Alder addition between chain-ends. The PCL/PEO content of the networks was varied by using PCL stars of different molar masses allowing tailoring the material hydrophilicity. We evidenced that the as-obtained hybrid networks exhibit not only excellent temperature-triggered shape-memory properties (high fixity and high and rapid recovery) but also valuable water-triggered shape-memory properties characterized by a high fixity and a recovery-rate controlled by the network composition. Remarkably, thanks to the introduction of thermo-reversible Diels–Alder adducts within the covalent network, we demonstrated that this material can be easily recycled while preserving the shape-memory performances. Therefore, the reconfiguration of the so-called permanent shape is straightforward making this material a potential candidate for applications in water responsive medical devices. The hydrolytic stability of these networks was demonstrated over a period of one month of immersion in water at physiological pH.